The role of drug susceptibility testing in controlling drug resistant tuberculosis: Challenges and possibilities. (March 2015) - Hoffner, Sven
Abstract: Aim and objective: Multidrug-resistant Mycobacterium tuberculosis (MDR-TB) is an increasing public health problem, causing significant difficulties and costs for TB control programs. In some settings, as many as each second infectious TB case has MDR-TB. Reliable and timely detection of these cases is urgently needed. Unfortunately, globally most MDR-TB patients are not identified and will thus not receive appropriate therapy. They are clearly at risk to develop even more resistant TB and to transmit increasingly resistant M. tuberculosis strains. With today's knowledge, available diagnostic tools and epidemiological situation, it cannot be considered acceptable to wait for 8–10 weeks to know if a clinical isolate is drug susceptible or not. Thus, the generally used algorithm of isolation on solid media followed by subsequent DST on solid media must today be seen as obsolete. The objective of this presentation is to discuss the possibilities and limitations of more rapid alternatives. Methods: Different, more rapid alternatives to the time-consuming classical laboratory tests to detect drug-resistant TB were compared. These include automated liquid culturing systems and molecular techniques. Results and discussion: The most rapid and promising techniques are based on molecular detection of resistance-related mutations, especially when the assay is used for direct testing of a smear-positive sputum sample. In this case MDR-TB patients can be detected in 1–2 days which makes early initiation of effective drug combinations possible. Besides a number of locally developed assays, there are today two major commercial alternatives: GeneXpert from Cepheid and the line probe assays (LPA) from Hain Life Science. The Xpert system is the most rapid technique, and it was developed to be easy to use. It offers the simultaneous detection of M. tuberculosis and resistance to rifampicin, which is seen as a proxy for MDR-TB. Rifampicin is, however, not everywhere an applicable MDR marker. For example, in Iran, the prevalence of rifampicin mono-resistant M. tuberculosis is high. The LPA investigates resistance to both rifampicin and isoniazid and is thus more informative. It is, however, somewhat more time-consuming and laborious to perform. Both assays have demonstrated excellent specificity and sensitivity. An exception to the high sensitivity is, however, seen in so-called hetero-resistant TB, where phenotypic DST assays are shown to be more sensitive to detect a small proportion of drug-resistant bacteria. Conclusions: Reliable and timely detection of drug-resistant TB is needed, which is best achieved with molecular assays. In this author's opinion, rapid detection of resistance to isoniazid should be included with rifampicin resistance examination. In MDR, timely detection of the XDR defining agents and PZA is urgently needed. Development and validation of such tests should be a priority, as well as establishing QMS for the implementation and routine use of molecular rapid diagnostics. Each country should develop national diagnostic algorithms for how, when and where rapid molecular assays should be used for early detection of drug-resistant TB.